2021
DOI: 10.1136/bmjopen-2020-044321
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and religion in residents and inter-relationships with clinical practice and residency training: a scoping review

Abstract: ObjectivesWith the increased emphasis on personalised, patient-centred care, there is now greater acceptance and expectation for the physician to address issues related to spirituality and religion (SR) during clinical consultations with patients. In light of the clinical need to improve SR-related training in residency, this review sought to examine the extant literature on the attitudes of residents regarding SR during residency training, impact on clinical care and psychological well-being of residents and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 71 publications
0
4
0
2
Order By: Relevance
“…Analisando os casos de Síndrome de Burnout, esta pesquisa pode reafirmar os achados de outros autores da literatura, sugerindo que o fator religioso pode estar associado ao menor risco de desenvolver Burnout quando o indivíduo possui alguma crença (CHOW et al, 2021;CARNEIRO et al, 2019). Neste estudo, apesar de poucos casos positivos para a doença, notou-se que 75% foram de indivíduos que afirmaram não possuir religião.…”
Section: Discussionunclassified
“…Analisando os casos de Síndrome de Burnout, esta pesquisa pode reafirmar os achados de outros autores da literatura, sugerindo que o fator religioso pode estar associado ao menor risco de desenvolver Burnout quando o indivíduo possui alguma crença (CHOW et al, 2021;CARNEIRO et al, 2019). Neste estudo, apesar de poucos casos positivos para a doença, notou-se que 75% foram de indivíduos que afirmaram não possuir religião.…”
Section: Discussionunclassified
“… 97 Chow et al ’s scoping review of religion and spirituality in residents included discussion of the link between reduced burn-out and spirituality. 99 Sibeoni et al ’s systematic review and meta synthesis of physician’s views of burn-out includes aspects of spiritual health in ‘calmness or letting go’, but did not analyse spiritual health as an aspect of overall health. 100 These authors reported that individual factors (including spiritual) and relational factors were more important than organisational concerns in protecting medical doctors from burn-out.…”
Section: Discussionmentioning
confidence: 99%
“…That's why this research aimed to try to analyze the medical staff's sense of being prepared to provide spiritual care to patients. It is a significant problem because both medical staff and the patients notice the need for this type of intervention and point to its deficit [22,23].…”
Section: Introductionmentioning
confidence: 99%